A Common Language of Software Evolution in Repositories (CLOSER) - Garrity, Jordan; Cutting, David (Software, 2025)
Version Control Systems (VCSs) are used by development teams to manage the collaborative evolution of source code, and there are several widely used industry standard VCSs. In addition to the code files themselves, metadata about the changes made are also recorded by the VCS, and this is often used with analytical tools to provide insight into the software development, a process known as Mining Software Repositories (MSRs). MSR tools are numerous but most often limited to one VCS format and, therefore, restricted in their scope of application in addition to the initial effort required to implement parsers for verbose textual VCS output. To address this limitation, a domain-specific language (DSL), the Common Language of Software Evolution in Repositories (CLOSER), was defined that abstracted away from specific implementations while isomorphically mapping to the data model of all major VCS formats. Using CLOSER directly as a data model or as an intermediate stage in a conversion analysis approach could make use of all major repositories rather than be limited to a single format. The initial barrier to adoption for MSR approaches was also lowered as CLOSER output is a concise, easily machine-readable format. CLOSER was implemented in tooling and tested against a number of common expected use cases, including a direct use in MSR analysis, proving the fidelity of the model and implementation. CLOSER was also successfully used to convert raw output logs from one VCS format to another, offering the possibility that legacy analysis tools could be used on other technologies without any changes being required. In addition to the advantages of a generic model opening all major VCS formats for analysis parsing, the CLOSER format was found to require less code and complete parsing faster than traditional VCS logging outputs.